Understanding the Conceptual Framework of Pad Structural Modification for Disc Brake Squeal Noise Suppression Based on System’s Dynamic Response - M.S. Sulaiman; N. Abu Husain; A.R. Abu Bakar; M.K. Abdul Hamid; N.H. Ismail; K. Zakaria (Journal of the Society of Automotive Engineers Malaysia, 2023)
Brake squeal noise solutions have been an essential subject in the automotive industry. It is among the most prevalent issues with car braking systems. For decades, the braking force that relies on the frictional force provided by the contact between the friction pad and rotor is still being used, thus inheriting the same fundamental issue of friction-induced brake squeal noise. Many proposed solutions and methods have been available from many research papers and articles. This paper attempts to summarize the most relevant literature on existing studies and theories to help understand the conceptual framework of the brake pad structural modification methods to reduce brake squeal noise. The review covers the underlying principles of the mode- coupling theory, methodology, and the technique’s effectiveness on vibrational characteristics and behavior analysis. A visual representation of a conceptual framework is finally presented at the end of this paper. The system’s dynamics response study is found adequate to explain the relationship of structural pad modification towards the brake squeal noise propensity. However, more detailed reviews are required from the study of the system’s vibrational energy, another major factor for accurate prediction to thoroughly understand the fugitive phenomena of the disc brake squeal noise.